Experimental design using response surface methods for palm olein-based hydroxy-ether systhesis - Darfizzi Derawi (Penerbit Universiti Kebangsaan Malaysia, 2016)
Hydroxy-ether-POo was synthesised via alcoholysis reaction of epoxidized palm olein (EPOo). The experimental design was conducted using response surface methodology (RSM) based on 3 factors; reaction time, reaction temperature and catalyst loading. Responses such as percentage of conversion and percentage of yield were determined using statistical software ‘Design Expert 9’. Hydroxy-ether-POo showed the presence of proton peak attached to the carbon of ether (3.2, 3.5 ppm) and proton of the hydroxyl (4.8 ppm). The presence of carbon peak bonded to hydroxyl was detected at chemical shift 75 ppm and carbonyl carbon of ether at 72 ppm.